OBJECTIFICATION OF ERGONOMIC ASSESSMENT OF THE PILOT OPERATION ON THE BASIS OF “PHOTOSHOP – TECHNOLOGY” - Gorbunov, Volodymyr (Proceedings of National Aviation University (archive), 2014)
On the basis of information technology “Photoshop” the means of the objective ergonomic evaluation of the professional activity of pilot on piloting the plane has been developed. Procedural characteristics, peculiarities and objective criteria if his work on aviation equipment is ergonomically acceptable, as well as the order of revealing the ergonomic shortcomings of the arrangement of his working place that decrease the flight safety from the position of human factor have been determined